EVALUASI PROGRAM MUHADAROH DI SMK NEGERI 4 PAYAKUMBUH DENGAN MODEL EVALUASI CIPP - Haruna, Dennis; Rifki, Ahmad; Rusyunizal, Dori; Nadir, Nadir; Ilmi, Darul (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
The Muhadaroh Program at SMK Negeri 4 Payakumbuh is an extracurricular activity aimed at developing students' public speaking skills and character, but its effectiveness has never been systematically evaluated. This study focuses on evaluating the Muhadaroh program using the CIPP model (Context, Input, Process, Product) to determine the relevance, resource readiness, implementation, and overall outcomes of the program. The research method employs a quantitative approach with data collection techniques including questionnaires, observations, and interviews with students and program instructors. The evaluation results indicate that in terms of context, the program is highly relevant to students' needs; in terms of input, the program is supported by adequate resources but not yet optimized; the process aspect shows routine implementation but not yet maximized student participation; and in terms of product, the program has a positive impact on students' self-confidence and communication skills, although not yet evenly distributed. In conclusion, Muhadaroh is a strategic program worthy of further development through enhanced teacher training, provision of supporting facilities, and a sustainable evaluation system to ensure equitable and comprehensive outreach to all participants.